Diversity and distribution of Primula species in western Arunachal Pradesh, eastern Himalayan region, India - Amal Bawri; Padma Raj Gajurel; Ashish Paul; Mohamed Latif Khan (Journal of Threatened Taxa, 2015)
The paper highlights the diversity, distribution and population status of Primula species in western Arunachal Pradesh. The present study has established the rich diversity of Primula species in western Arunachal Pradesh with a record total of 25 species, out of which five species, viz., Primula ioessa W.W.Sm., Primula munroi Lindley, Primula obliqua W.W.Sm., Primula prolifera Wall. and Primula jigmediana Hook. f. & Thomson ex Watt, are new to Arunachal Pradesh.  More than 60% of the taxa of Primula of the state occurs in two districts of the western part of the state.  A maximum diversity (76%) of Primula species was recorded between 3500m and 4000m and a minimum (4%) was between 1500m and 2000m.  This study showed the poor population of some Primula species in the study area.  Among the four sampling sites the Panga-Teng-Tso is highly disturbed which is clearly reflected by very poor population density of P. hookeri (1.36 individuals m-2). Various natural and anthropogenic threats have led to the pressure on the habitat of Primula species. Considering the rich species diversity of Primula and their distributional affinities, western Arunachal Pradesh may be considered as a centre of diversity of Indo-Chinese Primula species and appropriate conservation strategies should be adopted for the conservation of this genus.